Primary cilia biogenesis and associated retinal ciliopathies. (February 2021) - Chen, Holly Y.; Kelley, Ryan A.; Li, Tiansen; Swaroop, Anand
Graphical abstract: Abstract: The primary cilium is a ubiquitous microtubule-based organelle that senses external environment and modulates diverse signaling pathways in different cell types and tissues. The cilium originates from the mother centriole through a complex set of cellular events requiring hundreds of distinct components. Aberrant ciliogenesis or ciliary transport leads to a broad spectrum of clinical entities with overlapping yet highly variable phenotypes, collectively called ciliopathies, which include sensory defects and syndromic disorders with multi-organ pathologies. For efficient light detection, photoreceptors in the retina elaborate a modified cilium known as the outer segment, which is packed with membranous discs enriched for components of the phototransduction machinery. Retinopathy phenotype involves dysfunction and/or degeneration of the light sensing photoreceptors and is highly penetrant in ciliopathies. This review will discuss primary cilia biogenesis and ciliopathies, with a focus on the retina, and the role of CP110-CEP290-CC2D2A network. We will also explore how recent technologies can advance our understanding of cilia biology and discuss new paradigms for developing potential therapies of retinal ciliopathies.